Facilitaded and supervised learning program in functional neuroanatomy: experiences in a reference hospital in the Amazon (Research, Society and Development, 2023)
Objective: Stimulate in the student the humanized attendance, to recognize affections of the nervous system, to improve the analysis of laboratory and imaging tests, directed pre and postoperative care, recognize the importance of care bureaucracy for the proper functioning of the hospital service.  Method: This is a descriptive study of the type experience report, elaborated based on the experiences of a group of by approval in the selection process of the Facilitated and Supervised Learning Program of Functional Neuroanatomy in a large hospital and reference in neurology and neurosurgery in the Amazon Region. Results: The internship experience became opportune to provide continuity to the learning in neuroanatomy, semiology and neurological radiology, demands related to the neurologist’s practice, as well as indications of the various neurosurgical approaches. In the hospital, activities occurred daily in different sectors: Outpatient, Ward, Surgical Block, Intensive Care Unit and Hospital Management. Conclusion: The Facilitated and Supervised Learning Program in Functional Neuroanatomy was an excellent tool for the construction of essential pillars in the academic training of medical students and Consequently, it will positively impact the professional career in both the public and private sectors.